2004
DOI: 10.2746/0425164044864714
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of respiratory function by impulse oscillometry in horses

Abstract: Reasons for performing study: Due to technical implementations and lack of sensitivity, pulmonary function tests are seldom used in clinical practice. Impulse oscillometry (IOS) could represent an alternative method. Objectives: To define feasibility, methodology and repeatability of IOS, a forced oscillation technique that measures respiratory resistance (Rrs) and reactance (Xrs) from 5 to 35 Hz during spontaneous breathing, in horses. Methods: Using 38 healthy horses, Rrs and Xrs reference values were defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Pulmonary function was evaluated at rest before the treadmill test by impulse oscillometry in each horse without sedation (van Erck and others 2004). Total respiratory resistance (Rrs) and reactance (Xrs) at 5 and 10 Hz were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary function was evaluated at rest before the treadmill test by impulse oscillometry in each horse without sedation (van Erck and others 2004). Total respiratory resistance (Rrs) and reactance (Xrs) at 5 and 10 Hz were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite providing an objective measure of airway mechanics, these traditional methods have the disadvantages of being relatively expensive and invasive, necessitating the measurement of either intraoesophageal or intrapleural pressures. Furthermore, the sensitivity of these methods is relatively poor as changes consistent with the presence of airway obstruction are generally evident only when relatively severe and often clinically apparent . Consequently, alternative more sensitive methods have been evaluated in recent years.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%
“…Consequently, alternative more sensitive methods have been evaluated in recent years. These include impulse oscillometry, which measures respiratory resistance and reactance at various frequencies , tidal breathing flow‐volume loops , volumetric capnography and forced expiratory flow‐volume curve analysis , with the most discriminatory and commonly employed method at present being impulse oscillometry.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%
“…For the same reason, and as suggested previously [ 17 ], only impedance data showing high values of coherence (>0.85 at 3 Hz and >0.9 at 5 and 7 Hz) were included, in order to optimize the quality of data. Other studies on IOS values in horses with asthma did not report the coherence values [ 13 , 14 , 15 , 16 , 18 ], and therefore the comparison with our data is not possible.…”
Section: Discussionmentioning
confidence: 60%
“…The Impulse Oscillation System (IOS) is a method based on a repetition of impulses generated from a loudspeaker and applied to the respiratory system that allows the determination of R and X across multiple frequencies [ 12 ]. Van Erck et al [ 13 , 14 , 15 , 16 ] first reported on the use of IOS in horses with severe asthma, in which they evaluated the frequencies from 5 to 20 Hz. They reported that the results of IOS and conventional lung mechanics were well correlated.…”
Section: Introductionmentioning
confidence: 99%